UPEC strain characterization isolated from Mexican patients with recurrent urinary infections - Rosario Morales-Espinosa; Rigoberto Hernandez-Castro; Gabriela Delgado; Jose Luis Mendez; Armando Navarro; Angel Manjarrez; Alejandro Cravioto (Journal of Infection in Developing Countries)
Introduction: Any microorganism is capable of causing urinary tract infections (UTI). However, Uropathogenic Escherichia coli (UPEC) is responsible for the majority of UTI. A variety of virulence genes have been identified in UPEC. Diverse epidemiological studies support that specific subsets of genes are characteristic of each E. coli uropathogenic subtype involved in the development of cystitis, pyelonephritis, and urosepsis. Methodology: Twenty-three E. coli strains isolated from women with cystitis, 25 from men with prostatitis were characterized according to serotype, virulence genes, PFGE profile and susceptibility antimicrobials. Results: E. coli O25:H4–ST131 was more frequently isolated from cystitis than prostatitis. The majority of cystitis strains presented almost all the virulence genes, contrary to 60% of prostatitis strains. The strains characterized by serology, PFGE and MLST and virulence profile showed that cystitis strains shared a lineage with their own genomic fingerprint, indicating that these strains derived from a common ancestor. The prostatitis strains showed serotypes diverse and much higher degree of genetic diversity, indicating that they are an unrelated group.  More than 50% of isolates were resistant to at least 7 of the antimicrobials tested. Antibiotic-tolerant cells were observed, presenting with more frequency in response chloramphenicol, tetracycline, trimethoprim-sulfometoxazole and dicloxicillin. Conclusions: Persister cells can be detected from the beginning of the infection. The importance of these persister cells that exhibit multidrug tolerance is that a single surviving bacterium can initiate again an infection making it clinical relevant in the chronic urinary tract infection.